2018
DOI: 10.1016/j.amjcard.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cardiorespiratory Fitness on Risk of Sudden Cardiac Death in Overweight/Obese Men Aged 42 to 60 Years

Abstract: The purpose of this study was to examine the subject and combined associations of cardiorespiratory fitness (fitness) and body mass index (BMI) with the risk of sudden cardiac death (SCD) in middle-aged men. This prospective study was based on a population sample of 2,357 men aged 42 to 60 years, who were followed up in the Kuopio Ischemic Heart Disease cohort study. Fitness was directly measured by peak oxygen uptake (VO) during progressive exercise testing to volitional fatigue. Participants were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Heffernan and Loprinzi 4 concluded that maintaining higher CRF and lower body fat promotes healthy vascular aging, whereas the coexistence of lower CRF and high levels of obesity may accelerate vascular aging. Recently, Jae et al 8 reported that overweight/obesity and low levels of CRF were independently associated with the increased risk of sudden cardiac death in men; however, higher fitness appeared to attenuate this risk even in overweight/obese men. Collectively, these findings highlight the importance of improving CRF to attenuate the negative impact of obesity on vascular aging, which may ultimately confer a reduction in the risk of CVD events.…”
Section: Background and Study Overviewmentioning
confidence: 99%
“…Heffernan and Loprinzi 4 concluded that maintaining higher CRF and lower body fat promotes healthy vascular aging, whereas the coexistence of lower CRF and high levels of obesity may accelerate vascular aging. Recently, Jae et al 8 reported that overweight/obesity and low levels of CRF were independently associated with the increased risk of sudden cardiac death in men; however, higher fitness appeared to attenuate this risk even in overweight/obese men. Collectively, these findings highlight the importance of improving CRF to attenuate the negative impact of obesity on vascular aging, which may ultimately confer a reduction in the risk of CVD events.…”
Section: Background and Study Overviewmentioning
confidence: 99%